2014
DOI: 10.3109/02713683.2014.892998
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α(g.−308 G > A) andADIPOQ(g. + 45 T > G) Gene Polymorphisms in Type 2 Diabetes and Microvascular Complications in the Region of Punjab (North–West India)

Abstract: Our results indicated a higher risk of T2D and DR in the background of ADIPOQ TT genotype. Further, the ADIPOQ g. + 45 T > G and TNF-α g. - 308 G > A polymorphisms jointly give 1.45-fold risk towards T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
2
25
0
1
Order By: Relevance
“…In contrast, Ma et al found no independent role of rs2241766 in nephropathy development among Swedish Caucasians [25]. Neither did in three other studies by Sikka et al, Peng et al, and Rudofsky et al, respectively [27,30,31].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, Ma et al found no independent role of rs2241766 in nephropathy development among Swedish Caucasians [25]. Neither did in three other studies by Sikka et al, Peng et al, and Rudofsky et al, respectively [27,30,31].…”
Section: Discussionmentioning
confidence: 93%
“…During the further reviewing, 163 articles were deleted for editorials (7), on rats (6), not about DN or merely about diabetes (63), obvious irrelevancy (71), concerning the prognosis of DN (8), meta-analysis (3), and with no detailed data about genotype and allele frequencies (5). At last, 14 case-control studies with 3343 cases and 7859 controls were incorporated into the present meta-analysis [1,20,[24][25][26][27][28][29][30][31][32]. All of the controls in our meta-analysis were diabetic patients without nephropathy.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…However, the values of lipid parameters were not significantly different between T2D and control subjects in Jat Sikhs. These variations might be observed due to consumption of saturated fat and intensive lifestyle modifications and ethnic differences (Arnold et al 2009;Matharoo et al 2013;Sikka et al 2014). The increased fat consumption makes it harder for the body to absorb fat from the blood which might in turn increase the blood glucose concentrations and cause the liver to become resistant to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study had shown association of this SNP to DR but in conjunction with another gene polymorphism found in the ADIPOQ gene (rs2241766) (Sikka et al. ). Yoshioka et al.…”
Section: Chronic Hyperglycaemiamentioning
confidence: 86%
“…However, Sikka et al. () found an association with the TT genotype of rs2241766 in their cohort of Punjabi patients with DR.…”
Section: Chronic Hyperglycaemiamentioning
confidence: 90%